1998
DOI: 10.1177/088307389801300304
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Phase Neurologic Complications of Haemophilus Influenzae Type b Meningitis: Association With Developmental Problems at School Age

Abstract: The purposes of this study were to describe the incidence of acute-phase neurologic complications in a sample of 126 children with Haemophilus influenzae type b meningitis, and to determine if these complications were associated with higher rates of learning and behavior problems at school age. Risks were assessed by comparing rates of adverse psychoeducational outcomes in the 53 children in the sample with complications to corresponding outcome rates in the 67 children who were free of neurologic complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
20
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
4
20
2
Order By: Relevance
“…Most of the risk factors found in our study have been reported previously (2,6,7,9,11,(13)(14)(15). However, these authors all studied death or severe sequelae simultaneously with academic and/or behavioural limitations as outcome, and none of these studies provided a prediction rule to detect children at high risk for these limitations (2,6,7,9,11,(13)(14)(15).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Most of the risk factors found in our study have been reported previously (2,6,7,9,11,(13)(14)(15). However, these authors all studied death or severe sequelae simultaneously with academic and/or behavioural limitations as outcome, and none of these studies provided a prediction rule to detect children at high risk for these limitations (2,6,7,9,11,(13)(14)(15).…”
Section: Discussionmentioning
confidence: 63%
“…However, these authors all studied death or severe sequelae simultaneously with academic and/or behavioural limitations as outcome, and none of these studies provided a prediction rule to detect children at high risk for these limitations (2,6,7,9,11,(13)(14)(15). Furthermore, most studies included children with Hib meningitis (2,6,9,11,13,15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations